2018
DOI: 10.1063/1.5052559
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution and bonding properties of BSin−/ (n = 4–12) clusters: Size-selected anion photoelectron spectroscopy and theoretical calculations

Abstract: Size-selected anion photoelectron spectroscopy and theoretical calculations were used to investigate the structural evolution and bonding properties of BSi n −/0 (n = 4-12) clusters. The results showed that the B atom in BSi 4-12 −/0 prefers to occupy the high coordination sites to form more B-Si bonds. The lowest-lying isomers of BSi 4-7 −/0 primarily adopt bowl-shaped based geometries, while those of BSi 8-12 −/0 are mainly dominated by prismatic based geometries. For anionic clusters, BSi 11 − is the critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…The B n Si m clusters approach cage structures as the number of Si increases. 29,33,34,62 With m > n, the clusters would be equivalent of B n (BH) m clusters, i.e., with a greater number of boron atoms attached with H atoms. Here, with an increase in number of Si atoms, more electrons are removed from skeletal orbitals to Si lone pair orbitals.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
“…The B n Si m clusters approach cage structures as the number of Si increases. 29,33,34,62 With m > n, the clusters would be equivalent of B n (BH) m clusters, i.e., with a greater number of boron atoms attached with H atoms. Here, with an increase in number of Si atoms, more electrons are removed from skeletal orbitals to Si lone pair orbitals.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
“…Changes in composition of silicon materials, that is the incorporation of dopants such as boron or phosphorus, are typically achieved by admixture of diborane(6) (B 2 H 6 ) or phosphane (PH 3 ) at a late stage of silicon purification for band gap engineering in the crystalline state. The superconductivity of cubic silicon at high boron concentrations and temperatures near 0 K constitutes an extreme manifestation of the effect of heteroatoms on electronic properties of silicon . While a few stable examples of heterosiliconoids containing heavier Group 14 elements, namely, germanium and tin, are known, related species with Group 13 and/or 15 elements have so far only been observed in the gas phase or were calculated theoretically. We recently reported the functionalization of the dismutational isomer ( 1 ) and the global minimum isomer ( 2 ) of the still hypothetical hexasilabenzene by reductive cleavage of one of the aryl substituents (Scheme ). As distinct functionalized derivatives of 2 were obtained regiospecifically in both cases, , the peculiar stability of this type of Si 6 scaffold became once more obvious.…”
Section: Introductionmentioning
confidence: 99%
“…Our first and foremost note is that the most stable anionic I.B 2 Si 3 − structure (Figure 1) located in the present study was not found in the previous report by Lu and co-workers. 41 The anionic isomer II.B 2 Si 3 − , which was assigned as the global minimum of B 2 Si 3 − by these authors, 41 is now found at 2.7 kcal/mol higher in energy than the new I.B 2 Si 3 − , even though it remains competitive for the ground state in view of such a small energy difference. Such an omission by Lu et al 41 could have been due to the fact that they used the B3LYP functional in their search for stable structures.…”
Section: ■ Computational Methodsmentioning
confidence: 94%
“…41 The anionic isomer II.B 2 Si 3 − , which was assigned as the global minimum of B 2 Si 3 − by these authors, 41 is now found at 2.7 kcal/mol higher in energy than the new I.B 2 Si 3 − , even though it remains competitive for the ground state in view of such a small energy difference. Such an omission by Lu et al 41 could have been due to the fact that they used the B3LYP functional in their search for stable structures. Indeed, Koukaras 42 subsequently showed the erroneous performance of this hybrid functional on geometries of mixed boron clusters.…”
Section: ■ Computational Methodsmentioning
confidence: 94%
See 1 more Smart Citation